Using Facebook group in teaching listening of English for accounting - Fitria Nur Hamidah (Jurnal Linguistik Terapan, 2017)
Facebook is an alternative media for teaching listening of English for Accounting. The aims of this study are to examine the kinds of listening teaching and learning activities in English for accounting class which carried out via Facebook group and to describe the use of Facebook group in facilitating listening teaching and learning for English for accounting class based on the students’ perception. Facebook (FB) group is one of features that is available on Facebook social networking site. This feature allows for an unlimited number of members to participate, communicate and interact via post and chatting style especially for supporting ESP teaching and learning process in listening teaching and learning process. The FB groups which were created by the chief of the classes were usually used by the lecturer and the students in the class. Using Facebook (FB) group in teaching listening of English for Accounting class in Polytechnic of Kediri was very useful for the lecturer and the students of accounting.